Plakophilins and their roles in diseased states - Hofmann, Ilse (Cell & tissue research, 2020)
Tissue homeostasis is maintained by several cellular mechanisms and an imbalance may lead to diseased states. Here, the plakophilins 1, 2 and 3 operate as structural components and stabilize desmosomal cell-cell contacts. In their non-junctional states, they serve as regulators of signaling programs and control varied cellular processes that range from transcription, mRNA abundance, protein synthesis, growth, proliferation, migration to invasion and tumor development. Accordingly, mutations in plakophilins 1 and 2 lead to skin or heart diseases. Corresponding to their strong impact on tissue homeostasis, the expression of plakophilins is specifically deregulated in various cancer types and can be correlated with patients’ survival. However, our understanding on how plakophilins contribute to tumor development, progression and metastasis in a given tumor is still in its infancy and further in-depth studies using patient-derived data together with in vitro data and animal models are required.
Published online: 17 December 2019
Gesehen am 09.04.2020